Cholangitis caused by surgical clip migration into the common bile duct: a rare complication of a daily practice. Issue 1 (21st January 2020) - Sheffer, Daniel; Gal, Oren; Ovadia, Baruch; Kopelman, Yael
Abstract : A 54-year-old female patient complained of right upper quadrant abdominal pain 11 years following a laparoscopic cholecystectomy. A CT scan demonstrated a collection in the surgical bed and a surgical clip in the proximal bile duct. Cholangitis developed a few days later. Another CT showed that the surgical clip migrated to the distal common bile duct. The clip was removed by endoscopic retrograde cholangiography and the cholangitis was resolved.